How Can Nurses Help People with PTSD Cope with Their Symptoms? - Adams, Collette (2012)
Background Nurses, both general and mental health, are likely to come into contact with people with PTSD; with approximately 8% of men and 20% of women who experience a traumatic event going on to develop PTSD; and a wide range of traumatic events that can lead to the development of PTSD including: assault, road-traffic accidents, traumatic childbirth and being given a life threatening diagnosis of cancer. The NICE guidelines advise that individuals suffering from PTSD should be offered either trauma-focused cognitive behavioural therapy or eye movement desensitisation reprocessing as first-line treatments. However, not all sufferers are suitable for these treatments; if they are not yet ready to discuss their trauma, or if they have very high levels of distress or disassociation. Nurses will still need to assist these patients in managing their symptoms. Aim To review the literature on PTSD and identify what nurses can do to help patients cope with the specific symptoms that are causing them the most difficulties. Results The review highlights how culture influences the expression and treatment needs of PTSD sufferers. It also demonstrated how neurobiological changes in PTSD can inform nursing care. The review identified several components of trauma-focused cognitive behavioural therapy and eye movement desensitisation reprocessing that were associated with a reduction in PTSD symptoms, which can be used by nurses to support patients with PTSD. Conclusion There are clear implications for nursing practice, and the review suggests how nurses can help PTSD sufferers who are not yet ready for trauma-focused treatments; as well as how they can support patients that are engaged in trauma-focused therapy by reinforcing key principles of treatment.